Elastic flexural rigidity of steel-concrete composite columns. (1st April 2018) - Denavit, Mark D.; Hajjar, Jerome F.; Perea, Tiziano; Leon, Roberto T.
Highlights: Flexural rigidity of steel-concrete composite columns is quantified computationally. Effect of structural and loading parameters is investigated. Simple and robust values for design are proposed. Abstract: The use of elastic analysis is prevalent in the design of building structures even under loading conditions where inelasticity would be expected. Accordingly, geometric and material properties used in the elastic analyses must be carefully selected to maintain accuracy. Steel-concrete composite columns experience different forms of inelasticity. Concrete cracking is the source of much of the inelasticity and occurs at relatively low levels of load, but partial yielding of the steel, slip between concrete and steel, and concrete crushing also contribute to losses in stiffness. In this paper, the behavior of composite columns is characterized at the cross section and member levels through comparisons between inelastic and elastic analyses. Then, through a broad parametric study, specific practical design recommendations are developed for the elastic flexural rigidity of composite columns for the determination of lateral drifts under service loads. The recommendations in this paper provide simple and robust values for the stiffness of composite columns to be used for drift computations involving lateral loads.